MELALUI MINAT BACA REFERENSI KEPENDIDIKAN DI PERPUSTAKAAN SEKOLAH DAPAT MENINGKATKAN KOMPETENSI DAN KINERJA GURU DALAM MENGAJAR DI MADRASAH TSANAWIYAH SWASTA NURUL IMAN SELAYANG LANGKAT SEMESTER GANJIL TAHUN PELAJARAN 2022/2023 - Nurman Nurman (Jurnal Guru Kita PGSD, 2023)
Through Interest in Reading Educational References in the School Library Can Increase Teacher Competence and Performance in Teaching at Private Madrasah Tsanawiyah Nurul Iman Selayang Langkat Odd Semester 2022/2023 Academic Year. This research is using a type of quantitative research with 10 respondents as a sample. Management of hypothesis testing data using product moment analysis and t test. The research results show that; 1). Through Interest in Reading Educational References in the School Library Can Improve Teacher Competence in Teaching at Private Madrasah Tsanawiyah Nurul Iman Selayang Langkat Odd Semester 2022/2023 Academic Year, this can be seen from the results of calculating the initial activities of the first cycle with a validity value of 0.653 and a Test value t is 2.589, following the second cycle to the third cycle, with a validity value of 0.843 (very valid category) and a t-test value of 4.699 (very significant category). 2). Through Interest in Reading Educational References in the School Library Can Improve Teacher Performance in Teaching at Private Madrasah Tsanawiyah Nurul Iman Selayang Langkat Odd Semester 2022/2023 Academic Year, this can be seen from the results of calculating the initial activities of the first cycle with a validity value of 0.702 and a Test value t is 2.959, following the second cycle to the third cycle, with a validity value of 0.851 (very valid category) and a t-test value of 4.853 (very significant category). while all the calculated results are greater than the table results, the r table is 0.317 and the t table is 0.727.